Optimization of In-Vitro Tissue Culture and Transformation System for Sweet Sorghum Cultivars Using Immature Inflorescence - Abushal, Logayn (AUC Knowledge Fountain, 2021)
Background: Sweet sorghum is a multi-purpose crop that can be used for human food, animal feed, and bio-fuel production. This crop is drought-tolerant and can therefore be grown in arid and semi-arid regions especially in marginal areas in Egypt. Nevertheless, production of Sweet sorghum cannot coup with the increasing demand in consumption as a food, and fuel due to a lag in scientific research regarding its genetic improvement. Therefore, genetic improvement of Sweet sorghum is innately required so that new traits of economic importance could be introduced; however, this can only be achieved through the establishment of a robust in-vitro tissue culture system. Thus, this study aimed to establish an effective regeneration system for three different Sweet sorghum cultivars namely; Rex, Sugar Drip, and Ramada, using immature inflorescence explants. Subsequently, the cultivar Sugar was selected to examine its transformation efficiency using the microprojectile bombardment technology. Methods: For callus induction media, explants from immature inflorescences of different lengths (1.5- 16 cm), were grown over a combination of 2,4-D (0, 2, 4 & 6mg/L) with kinetin (0, 0.2 & 0.5mg/L). For regeneration media, BAP was the main cytokinin implemented in the three different treatments along with either: NAA, IAA, or IAA & TDZ, whereas TDZ was employed alone in a fourth treatment. The transformation system of the cultivar Sugar Drip was also developed using immature inflorescence explants. Co-bombardment was performed using the neomycin phosphotransferase II (nptII) gene under the control of maize ubiquitin (Ubi1) promoter. The selection of putative transgenic plants was performed using paromomycin antibiotic. Results: The best embryogenic callus induction frequency was observed in Rex (77%) on modified MS media supplemented with 4mg/L 2,4-D + 0.2mg/L kinetin after six weeks from culture. However, Ramada and Sugar Drip had their highest callus induction rates of 93 and 94%, respectively, when 6mg/L 2,4-D + 0.2mg/L kinetin was used. The addition of 1mg/L IAA + 0.5mg/L BAP + 0.1mg/L TDZ had its best outcome in terms on shoot induction, shoot/callus number, and root formation. In Sugar Drip transformation, paromomycin eliminated most the non-transgenic plants from the putative transgenic ones. Eventually, 6 out of 348 bombarded samples were found to be transgenic after PCR screening. The percentage of transformation from two independent experiments was around 1.724%. Conclusion: PCR analysis of putative transformants revealed a transformation efficiency of 1.724%. Therefore, genetic transformation using particle bombardment has shown to be a successful method for the transformation of immature Sweet sorghum inflorescences with relatively high success rates.